COMMUNICATING ANCIENT INDIAN CULTURE THROUGH MUSEUMS: WEBSITE ANALYSIS OF NATIONAL MUSEUM, NEW DELHI - Dubey, Abhishek (ShodhKosh: Journal of Visual and Performing Arts, 2023)
India is one of the eight ancient civilizations of the world. Harappa Civilisation was an epitome of rich cultural confluence. The National Museum, New Delhi is an autonomous organization of the Ministry of Culture, Government of India boasts of diverse cultural objects from India and abroad. NM plays a pivotal role in the promotion of India culture both inside and outside of the country by collaborating with national and international cultural organizations. Collection, Conservation and Communication (3Cs) are the cornerstone of its mission to promote the Indian culture. The focus of this paper is the last ‘C’ that is “Communication”. The present study is limited to the study of only ten artifacts belonging to the Indus Valley Civilisation which were judged on five cultural value indicators such as aesthetics, symbolic, spiritual, social, and educational. The mainstay of the study is the website content of the National Museum. The study reveals that these artifacts are well preserved. The images uploaded on the website are of good quality. But the scroll speed is slightly high and also the description does not accompany the images. Future studies may indulge on the website of analysis of other national/international museums to have wide perspective.